Modeling analysis of elastic properties of graphene‐carbon nanotube (G‐C) reinforced composites. Issue 5 (21st March 2022) - Zheng, Weipeng; Guo, Zhangxin; Wang, Zhihua; Boay, Chai Gin; Wang, Xiaojun; Li, Yongcun
Abstract: This article describes in detail the research on the elastic properties of carbon nanotube reinforced composite materials and graphene‐carbon nanotube (G‐C) reinforced composite materials. Several different composite material models were established using finite element software ABAQUS to study the influence of the inclination angle, quantity and volume fraction of carbon nanotubes and graphene on the elastic modulus of reinforced composites. The results show that as the volume fraction of graphene and carbon nanotubes increases, the Young's modulus and shear modulus of the reinforced composite material increase significantly. In addition, the tilt angle and quantity of graphene and carbon nanotubes will also affect the elastic properties of the composite material. The Young's modulus E and the shear modulus G decrease with the increase of the inclination angle, and increase with the increase of the number of graphene and carbon nanotubes. Abstract :